Preventing Co-occurring Intimate Partner Violence and Child Abuse in Eastern Democratic Republic of Congo: The Role of Family Functioning and Programmatic Reflections - Falb, Kathryn (Journal of interpersonal violence, 2023)
Co-occurring intimate partner violence (IPV) and child abuse occur at staggering levels in eastern Democratic Republic of Congo (DRC), yet little is known about the relationship between these forms of violence and a feminst-grounded conceptualization of family functioning nor how best to programmatically address these multiple forms of violence in the home. Analysis of cross-sectional baseline data from 203 adult couple dyads participating in a randomized controlled trial was undertaken to (1) understand the correlation of family functioning and violence in the home in North Kivu, DRC; (2) unpack potential shared correlates of violence in the home and family functioning, such as attitudes and behaviors; and (3) describe programmatic implications for delivering violence prevention programming that seeks to address multiple forms of violence in the home. Findings suggest over half of all families reported experiencing IPV against women or use of child abuse by any caregiver. Moderate levels of family functioning were also reported, although women reported lower levels. In adjusted models, a one-point change in family functioning score was associated with a 0.12 reduction in odds of co-occurring experience of IPV and use of child abuse for women, and a 0.03 reduction in odds of co-occurring perpetration for men. A focus on improving family functioning as a primary outcome, alongside explicit targeting of harmful gender norms and skills-based approaches, may be a promising avenue to integrate approaches from different violence prevention fields while maintaining a strong dedication to intersectional feminist-grounded approaches that allows for separate, but at times combined, approaches to reducing IPV and child abuse in the home.